2013
DOI: 10.1002/jso.23528
|View full text |Cite
|
Sign up to set email alerts
|

Axillary reverse mapping using fluorescence imaging is useful for identifying the risk group of postoperative lymphedema in breast cancer patients undergoing sentinel node biopsies

Abstract: BackgroundAxillary reverse mapping (ARM) is a novel technique for preserving the upper extremity lymphatic pathways during axillary lymph node surgery. However, there is no evidence of the usefulness of ARM for patients undergoing sentinel lymph node biopsy (SNB).MethodsBetween August 2009 and July 2012, 372 patients who underwent the SNB procedure for breast cancer were enrolled in this study. Using the indocyanine green fluorescence technique and indigocarmine blue dye method, we studied the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…The identification rates of ARM nodes were lower in the SLN biopsy field when compared with those in the ALND field. This is consistent with the results of other studies 11,12,20,30,34 (Table 2).…”
Section: Locations Of Sln and Arm Nodessupporting
confidence: 93%
See 3 more Smart Citations
“…The identification rates of ARM nodes were lower in the SLN biopsy field when compared with those in the ALND field. This is consistent with the results of other studies 11,12,20,30,34 (Table 2).…”
Section: Locations Of Sln and Arm Nodessupporting
confidence: 93%
“…Boneti et al 34 reported that crossover (ARM node ¼ SLN) occurred in only 6 (2.8%) of 218 patients, although ARM lymphatics were near or within the SLN biopsy field in 40.6% of patients. Nevertheless, other investigators reported concordance rates of 7.2%~28% between ARM nodes and SLN 14,16,19,20,26,27,30 (Table 2). In our recent study using fluorescence imaging, the ARM nodes were SLN-ARM nodes in 64 (27%) of 238 patients (unpublished data).…”
Section: Locations Of Sln and Arm Nodesmentioning
confidence: 94%
See 2 more Smart Citations
“…Cystoscopic mucosal injection with distension of the bladder (cases [9][10][11][12][13][14][15][16][17][18][19][20]. After cystoscopic mucosal injection and filling of the Preoperative tumour stage of based on cystoscopy biopsy.…”
Section: Sentinel Lymph Node Mappingmentioning
confidence: 99%